Ultraviolet radiation, both UVA and UVB, influences the composition of the skin microbiome. Issue 2 (14th January 2019) - Burns, Erin M.; Ahmed, Hana; Isedeh, Prescilia N.; Kohli, Indermeet; Van Der Pol, William; Shaheen, Abdullah; Muzaffar, Anum F.; Al‐Sadek, Camli; Foy, Thompson M.; Abdelgawwad, Mohammad S.; Huda, Sumeira; Lim, Henry W.; et al.
Abstract: Background: Studies have begun to investigate the complex relationship between host and microorganisms in non‐infectious pathologies such as acne, atopic dermatitis and psoriasis. Though the skin is exposed to environmental stressors such as ultraviolet radiation (UVR), no studies exist examining the effects of both UVA and UVB on the skin microbiome. Objective: To test the effect of UVA and UVB on human skin microbiome. Methods: To test whether UV will alter the cutaneous microbiome, participants were exposed to doses of UVA (22‐47 J/cm 2 ) or UVB (100‐350 mJ/cm 2 ) and samples were collected. DNA was isolated and sequenced to identify the microbial composition of each sample. Results: There was vast intra‐ and inter‐subject variation at all time points, and phylum and species‐level differences were identified. These included an increase in the phylum Cyanobacteria and a decrease in the family Lactobacillaceae and Pseudomonadaceae. The sensitivity of microbes to UVR and their re‐colonization potential following exposure differed in UVA vs UVB samples. Limitations: The sample size was small, and the study was limited to males. Conclusion: The results demonstrate that UVR has profound qualitative and quantitative influences on the composition of the skin microbiome, possibly effecting skin pathology in which UVR is a factor.